A consistent thermodynamic molecular model of n-hydrofluoroolefins and blends for refrigeration applications. (May 2020) - Albà, Carlos G.; Vega, Lourdes F.; Llovell, Fèlix
Highlights: A soft-SAFT molecular model is used to describe HFOs for refrigeration. Density, surface tension, derivative properties and viscosity are perfectly reproduced. Binary mixtures of HFOs and HFO-HFC are described in agreement with data. Thermodynamics of ternary mixtures are predicted without any fitting parameter. The CoP of several new mixtures is evaluated with process simulation. Abstract: This work presents a thermodynamic model that characterizes 4th-generation hydrofluoroolefins (HFOs)-based refrigerants with the molecular-based soft-SAFT equation of state (Blas and Vega, 1998) as well as its application in process simulations for a selected refrigeration application. The evaluation of the HFOs has been done building on a molecular model transferred from the equivalent hydrofluorocarbons (HFCs), taking advantage of the similarities between the two chemical families. The model has been used to calculate all thermophysical properties of the selected HFOs relevant for their application as refrigerants, including the saturated density, vapor pressure, heat capacity, speed of sound, surface tension and viscosity, providing good agreement with experimental available data. In addition, phase equilibria, interfacial behavior and viscosity calculations have been performed for blends between HFCs and the two most common HFOs, R1234yf and R1234ze(E). The obtained thermodynamic properties have been used for a process simulation of a vapor compression refrigeration system, comparing the 3rd generation refrigerant R410A with these 4th generation blends, including the Coefficient of Performance for different cases, in order to establish the best alternative to R410A. Overall, this work shows how molecular modeling tools can be used now a day, as a complementary tool to generate reliable data for process simulation, in this case related to the search for alternative refrigerants.